Attachment "Disorders": Capitalizing on Misfortune - Ross, Lynda R. (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
Attachment theory is the primary source informing Reactive Attachment Disorder (RAD) as well as providing the framework for other potential "attachment disorder" diagnoses. This paper provides an historical overview of the RAD construct and discusses the personal and social implications resulting from "disordering" conduct and separating normal from pathological behaviours.